Personal Managerial Effectiveness: Future Vision, Current Reality and Identification of Gaps and Strengths - Wahyudi, Slamet (Graduate Program Magister Manajemen Pendidikan, 2022)
This article focuses on the process on how an individual states future vision, current reality and finding the gaps between, in order to know his own strengths. Often we did not realize that our vision is too hard to achieve without considering the current reality. There are four tests I did to find out the gaps and strengths; these are including The McPhee Andrewartha, The Personality Test, The Big Five Test and Strength Finder. The result of the test shows some gaps and strengths for me to note. The four tests allow me to recognize some strength that I should work and improve. What is new here we focus only on the strengths we have, not the weaknesses. As pandemic is going on, effectiveness test could be a solution for us to perform better at the workplaces.